1253. Healthcare-Associated Transmission of Burkholderia cepacia Complex Associated With Extrinsically Contaminated Nasal Spray. (26th November 2018) - Tran, Dat; Cassidy, Maureen; Buehring, Tara; Pierce, Rebecca
Abstract: Background: Burkholderia cepacia complex (Bcc) species can contaminate medical devices and water-based products, resulting in outbreaks of healthcare-associated infections. In March 2018, we investigated a cluster of 20 patients with a sinus culture positive for Bcc seen at two affiliated ENT clinics in Oregon over a 2-month period, based on reporting by a laboratorian in a central laboratory external to the clinics. Methods: We conducted an epidemiologic investigation to identify potential causes for an apparent outbreak of Bcc, including review of health records and microbiologic reports, site visits, staff interviews, and cultures of common equipment and products. Results: 20 patients (9 were female; age range 10 to 72 years, median age 54.5 years) had new positive Bcc cultures from the sinus. The absence of cystic fibrosis, immunosuppression or sinonasal polyposis in all patients, scant growth of Bcc in most cases with isolation of another organism in some, and the use of Bcc-directed antibiotics in a minority of patients suggested the presence of a contamination source. All patients had received lidocaine/phenylephrine (L/P) via multidose nasal spray atomizers prior to endoscopically-directed sinus cultures. Site visits revealed improper medication dispensing and storage practices (e.g., no expiration date for L/P stock, storage of L/P-containing atomizers at room temperature), and inadequate instrument reprocessing and environmental cleaning. Cultures of L/P in 2/2 in-use atomizers and 1/1 opened stock bottle, as well as swabs of 3/3 spray mechanisms, grew Bcc. Cultures of L/P from the unopened, refrigerated stock bottle, a flexible endoscope and a rigid endoscope did not yield Bcc. No negative clinical sequelae in these patients were reported. Conclusion: Contaminated multidose L/P nasal spray with Bcc resulted in nosocomial transmission at these clinics. This investigation highlights the important role of laboratorians in detecting Bcc contamination events that lead to colonization, and suboptimal reporting by clinicians in the outpatient setting. It also raises the question of how often such contamination events go undetected. Injection safety training needs to be broadened to "medication administration safety" training as one and only principles could have prevented this incident. Disclosures: All authors: No reported disclosures.